Students' Perception Of The Effectiveness Of Running And Walking In Weight Loss Efforts (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Obesity and overweight have become significant health problems among university students due to sedentary lifestyles, low physical activity, and unhealthy dietary habits. Aerobic activities such as running and walking are widely recognized as effective strategies for weight loss because they increase energy expenditure and improve metabolic function. However, the effectiveness of these activities is not only influenced by physiological factors but also by individual perceptions, which may affect exercise participation and adherence. Therefore, this study aimed to analyze the perceptions of students from the Department of Sports Science at Universitas Negeri Semarang regarding the effectiveness of running and walking in weight loss efforts. This study employed a descriptive quantitative design using a survey approach. A total of 61 students were selected through purposive sampling techniques. Data were collected using a Likert-scale questionnaire designed to measure students’ perceptions of running and walking effectiveness for weight loss. The collected data were analyzed using descriptive statistics, including mean scores and standard deviations. The results revealed that students’ perceptions of running (33.08 ± 5.57) and walking (33.13 ± 4.62) were categorized as moderate. Most respondents demonstrated moderate levels of perception, indicating that their understanding of the effectiveness of both activities remains limited. Furthermore, students tended to perceive running and walking similarly, suggesting that both activities were viewed as relatively equal in supporting weight loss efforts. In conclusion, although aerobic exercise has been scientifically proven to support weight reduction, students’ perceptions regarding its effectiveness remain moderate. These findings indicate a gap between theoretical knowledge and practical perception, highlighting the need for more applicable and evidence-based educational strategies to improve students’ understanding of physical activity and weight management.